"SPEECH THERAPY WITH CHILDREN USING COCHLEAR IMPLANTS: EXPERIENCE AND METHODS" (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article examines the crucial role of speech therapy in maximizing the communication outcomes for children with cochlear implants (CIs). It reviews a range of evidence-based speech therapy approaches and methods tailored to the unique needs of CI recipients, encompassing auditory-oral therapy, auditory-verbal therapy, and combined approaches. The article details practical techniques for improving speech perception, articulation, phonology, voice quality, fluency, and overall speech intelligibility. It highlights the importance of early intervention, individualized treatment plans, family involvement, and ongoing assessment to monitor progress and adjust therapy strategies. Drawing on clinical experience and current research, this article provides valuable insights for speech-language pathologists and other professionals working to enhance the spoken language abilities of children with CIs.